Translating research into action: An evaluation of the World Trade Center Health Registry's Treatment Referral Program - Welch, Alice E (Disaster Health, 2014)
This manuscript describes the design, implementation and evaluation of the World Trade Center (WTC) Health Registry's Treatment Referral Program (TRP), created to respond to enrollees’ self-reported 9/11-related physical and mental health needs and promote the use of WTC-specific health care. In 2009–2011, the TRP conducted personalized outreach, including an individualized educational mailing and telephone follow-up to 7,518 selected enrollees who resided in New York City, did not participate in rescue/recovery work, and reported symptoms of 9/11-related physical conditions or posttraumatic stress disorder (PTSD) on their most recently completed Registry survey. TRP staff spoke with enrollees to address barriers to care and schedule appointments at the WTC Environmental Health Center for those eligible. We assessed three nested outcomes: TRP participation (e.g., contact with TRP staff), scheduling appointments, and keeping scheduled appointments. A total of 1,232 (16.4%) eligible enrollees participated in the TRP; 32% of them scheduled a first-time appointment. We reached 84% of participants who scheduled appointments; 79.4% reported having kept the appointment. Scheduling an appointment, but not keeping it, was associated with self-reported unmet health care need, PTSD, and poor functioning (≥14 days of poor physical or mental health in the past 30 days) (P < 0.05). Neither scheduling nor keeping an appointment was associated with demographic characteristics. Successful outreach to disaster-exposed populations may require a sustained effort that employs a variety of methods in order to encourage and facilitate use of post-disaster services. Findings from this evaluation can inform outreach to the population exposed to 9/11 being conducted by other organizations.